Death and Burial Rites and Ceremonies - oglu, Tugalov Boburjon Bahodir (European Journal of Life Safety and Stability (2660-9630), 2022)
In this article, the rituals associated with death. The article contains a set of death-related traditions of Uzbeks living in the territory of the Republic, as well as religious rules and rituals, as well as customs arising from the requirements of universal, vital needs.